Răspuns :
1)a)3x(-2)+(-6):(-1)=-6+6=0
b)2x{2x[2-(-6)x3]}=2x[2x(2+18)]=2x40=80
2)(-2)-[(-5)x6]=(-2)-(-30)=60
[14:(-2)]+10=-7+10=3
3)a)-2+15=13
b)-6-12:(+3)=-6-4=-10
c)12-40=-28
4)a)-30+10=-20
b)-7-2=-9
c)-16+4=-12
5a)-5+4=-1
b)-10=3=-7
c)-17+2=-15
7)a)-6+30=24
b)0+40=40
c)-15+5=-10
d)9-25=-16
e)-21-25=-46
f)6+60=66
Sper ca te-am ajutat! :D
b)2x{2x[2-(-6)x3]}=2x[2x(2+18)]=2x40=80
2)(-2)-[(-5)x6]=(-2)-(-30)=60
[14:(-2)]+10=-7+10=3
3)a)-2+15=13
b)-6-12:(+3)=-6-4=-10
c)12-40=-28
4)a)-30+10=-20
b)-7-2=-9
c)-16+4=-12
5a)-5+4=-1
b)-10=3=-7
c)-17+2=-15
7)a)-6+30=24
b)0+40=40
c)-15+5=-10
d)9-25=-16
e)-21-25=-46
f)6+60=66
Sper ca te-am ajutat! :D